MicroRNA-432 inhibits milk fat synthesis by targeting SCD and LPL in ovine mammary epithelial cells. Issue 19 (19th August 2021) - Hao, Zhiyun; Luo, Yuzhu; Wang, Jiqing; Hickford, Jon G. H.; Zhou, Huitong; Hu, Jiang; Liu, Xiu; Li, Shaobin; Shen, Jiyuan; Ke, Na; Liang, Weiwei; Huang, Zhaochun
Abstract : The miR-432 inhibits the proliferation of ovine mammary epithelial cells and milk fat synthesis by targeting SCD and LPL in sheep. Abstract : The microRNA (miR)-432 is differentially expressed in the mammary gland of two breeds of lactating sheep with different milk production traits, and between the non-lactating and peak-lactation periods, but there have been no reports describing the molecular mechanisms involved. In this study, the effect of miR-432 on the proliferation of ovine mammary epithelial cells (OMECs) and the target genes of miR-432 were investigated. The effects of miR-432 on the expression of the target genes and the content of triglycerides in the OMECs were also analyzed. Transfection with a miR-432 mimic was found using CCK8 and Edu assays, to inhibit the viability of OMECs and reduce the number of proliferated OMECs. In contrast, a miR-432 inhibitor had the opposite effect to the miR-432 mimic, and together these results suggest that miR-432 inhibits the proliferation of OMECs. A dual luciferase assay revealed that the genes for stearoyl-CoA desaturase ( SCD ) and lipoprotein lipase ( LPL ) are targeted by miR-432. The transfection of miR-432 mimic into OMECs resulted in decreases in the expression of SCD and LPL, and three other milk fat synthesis marker genes; FABP4, LPIN1 and ACACA . The mimic also decreased the content of triglycerides. The miR-432 inhibitor had the opposite effect to the mimic on the expression of these genes and the level of triglycerides. This is the first study to reveal the biological mechanisms by which miR-432 inhibits milk fat synthesis in sheep.